Nutrition status and associated factors among tribal preschool children of 2-5 years in five districts: a cross-sectional study from three states of India - Kumar, Dinesh; Saxena, Nishant; Srivastava, Suyesh; Haranahally Vasanthachar, Manjunathachar (International Journal Of Community Medicine And Public Health, 2024)
Background: To report the nutrition status in preschool children by 2-5 years of age among tribal children from five districts of India. Methods: Community based cross sectional study of 204 tribal households having a child aged 2-5 year from five Indian districts with a considerable proportion of the tribal population. Socio-demographic details, and nutrition status by anthropometric measurements of children were collected from mothers. The age, sex, height and weight data of children were analysed according to WHO child growth, 2006 criteria to estimate the nutritional status. Multiple logistic regression analyses were performed to identify the associated factors. Results: Only 56% preschool children (2-5 years) were having normal nutrition among the tribal children; 44% preschool children were found to be malnutrition. Of them, 27.9% (29.2% boys and 26.8% girls) were severely underweight (<-3SD), and 15.7% (13.5% boys and 17.6% girls) were underweight (-3SD to -2SD). The age-appropriate nutrition was unsatisfactory due to delay in breast feeding, nuclear family, child birth at home, mother education and non-availability of milk giving animal were the main reasons for malnutrition. Extended family, higher education of mothers and head of the household, hospital birth and breastfeeding immediately were significantly associated with normal nutrition. Conclusions: A relatively low proportion of children were normal nutrition among the tribal population. Socio-economic factors, mainly the parental education, extended family were significantly associated with a child being normal nutrition. Improving the socio-economic status is crucial, and there is a need to improve the nutrition coverage in tribal areas.